PENGEMBANGAN MEDIA PEMBELAJARAN PAKU SARAJA PADA MATERI AKSARA JAWA UNTUK SISWA KELAS IV SD - Nikmah Fitria Surya; Dhian Dwi Nur Wenda; Nurita Primasatya (Jurnal Muara Pendidikan, 2023)
This research is motivated by the results of observations made on fourth-grade students at SDN 1 Watudandang regarding students' difficulties in understanding and memorizing Javanese script. Some of the obstacles that arise include the limitations of learning tools and media. This research is Research and Development (Research & Development) with the ADDIE research model. The purpose of developing the Paku Saraja learning media (Javanese Script Cube Board) on Javanese Script material is to improve the learning outcomes of fourth-grade students at SDN 1 Watudandang. Data collection techniques used are questionnaires and questionnaires. The data analysis technique is a qualitative data analysis technique. Based on the results of the study, which included material validity tests by material experts obtained an average score of 92 with very good eligibility criteria. Then the media validity test by media experts obtained an average value of 95 with very good eligibility criteria. The teacher's practicality test of the media obtained a score of 97 with very good eligibility criteria. As well as the practicality test of the media by students obtaining a score of 97 with very good eligibility criteria. Based on the product effectiveness test, many student scores increased above the KKM, namely 15 students out of 18 students. So, it can be concluded that the Paku Saraja learning media is feasible and effective for use in learning.